Mapping the architecture of the ATP-binding site of the K(ATP) channel subunit Kir6.2 - Dabrowski, Michael (Blackwell Science Inc, 2004)
ATP-sensitive potassium (K(ATP)) channels comprise Kir6.2 and SUR subunits. The site at which ATP binds to mediate K(ATP) channel inhibition lies on Kir6.2, but the potency of block is enhanced by coexpression with SUR1. To assess the structure of the ATP-binding site on Kir6.2, we used a range of adenine nucleotides as molecular measuring sticks to map the internal dimensions of the binding site. We compared their efficacy on Kir6.2–SUR1, and on a truncated Kir6.2 (Kir6.2ΔC) that expresses in the absence of SUR. We show here that SUR1 modifies the ATP-binding pocket of Kir6.2, by increasing the width of the groove that binds the phosphate tail of ATP, without changing the length of the groove, and by enhancing interaction with the adenine ring.